Translation into Spanish and Proposal to Modify the Orchard Sports Injury Classification System (Osics) Version 12 - Cofre-Bolados, C (Elsevier Doyma, 2020)
Objective: To publish the Spanish translation of version 12 of the sports injury classification system called Orchard Sports Injury Classification System and propose a modification to include a numerical code which reflects the impact of the injury on sports functionality. Method: The members of the working group on the epidemiology of sports injury, of the Group for the Study of the Muscle-Tendon System (GESMUTE), and of the Spanish Society of Sports Traumatology (SETRADE), carried out a bibliographical review on the epidemiological classification systems of injuries, three face-to-face consensus meetings and various online pieces of work, following the DELPHI work methodology. Results: The Spanish translation of version 12 of the Orchard Sports Injury Classification System is fully accessible and free of charge at: https://gesmute.es/traduccion-espanola-osics-12/The current project proposes to add, at the end of the current coding system of version 12, a numerical code (0: No Functional impairment; 1: Limits Sports Activity; 2: Prevents Sports Activity; 3: Limits Daily Life Activities), to indicate any functional repercussions caused by the injury. Conclusions: We present the Spanish translation of version 12 of the Orchard Sports Injury Classification System. We propose as an improvement the inclusion of functionality criteria in sports injury classifications; more specifically, our proposal could be an improvement to the Orchard Sports Injury Classification System version 12. © 2020 FUTBOL CLUB BARCELONA and CONSELL CATALÀ DE L ESPORT